Nutritional Probing and HPLC Profiling of Roasted Date Pit Powder - Ahmed, Aftab; Arshad, Muhammad Umair; Saeed, Farhan; Ahmed, Rabia Shabir; Chatha, Shahzad Ali Shahid (Pakistan Journal of Nutrition, 2016)
Nature has miraculously blessed many plants with such phyto-chemical profile that is valuable for mankind in various ways. Some plant materials considered waste, contain valued phyto-chemicals advantageous for humans. One such material is date pit. In present research study, date pits from three geographically different date varieties (Ajwa from Saudi Arabia, Hallawi from Iran and Aseel from Pakistan) were selected and their pits were roasted and ground into powder. The aim of this study was to determine chemical & mineral profile, dietary fibre, total phenolics, total flavonoids and total antioxidant activity of roasted date pits. Ajwa contained higher amounts of crude proteins, crude fats and crude fiber. The date pits of Ajwa varieties were also containing the higher amounts of dietary fiber especially insoluble fiber. Furthermore phenolic profiling of roasted date pits detected 10 different phenolic compounds through HPLC studies. The date pits contain higher amounts of gallic acid, chlorogenic acid and ferulic acid. However, their highest amounts were recorded in Ajwa i.e., 175.13±7.45, 82.88±3.87 and 61.46±2.81 mg/kg, respectively. The data collected from the current investigation recommend Ajwa date pits to be considered as a functional food ingredient owing to potentially excellent source of natural antioxidants.